Association of polygenic liabilities for schizophrenia and bipolar disorder with educational attainment and cognitive aging - Chi-Shin Wu; Chia-Lin Hsu; Mei-Chen Lin; Mei-Hsin Su; Yen-Feng Lin; Chia-Yen Chen; Po-Chang Hsiao; Yi-Jiun Pan; Pei-Chun Chen; Yen-Tsung Huang; Shi-Heng Wang (Translational Psychiatry)
Abstract To elucidate the specific and shared genetic background of schizophrenia (SCZ) and bipolar disorder (BPD), this study explored the association of polygenic liabilities for SCZ and BPD with educational attainment and cognitive aging. Among 106,806 unrelated community participants from the Taiwan Biobank, we calculated the polygenic risk score (PRS) for SCZ (PRSSCZ) and BPD (PRSBPD), shared PRS between SCZ and BPD (PRSSCZ+BPD), and SCZ-specific PRS (PRSSCZvsBPD). Based on the sign-concordance of the susceptibility variants with SCZ/BPD, PRSSCZ was split into PRSSCZ_concordant/PRSSCZ_discordant, and PRSBPD was split into PRSBPD_concordant/PRSBPD_discordant. Ordinal logistic regression models were used to estimate the association with educational attainment. Linear regression models were used to estimate the associations with cognitive aging (n = 27,005), measured by the Mini-Mental State Examination (MMSE), and with MMSE change (n = 6194 with mean follow-up duration of 3.9 y) in individuals aged≥ 60 years. PRSSCZ, PRSBPD, and PRSSCZ+BPD were positively associated with educational attainment, whereas PRSSCZvsBPD was negatively associated with educational attainment. PRSSCZ was negatively associated with MMSE, while PRSBPD was positively associated with MMSE. The concordant and discordant parts of polygenic liabilities have contrasting association, PRSSCZ_concordant and PRSBPD_concordant mainly determined these effects mentioned above. PRSSCZvsBPD predicted decreases in the MMSE scores. Using a large collection of community samples, this study provided evidence for the contrasting effects of polygenic architecture in SCZ and BPD on educational attainment and cognitive aging and suggested that SCZ and BPD were not genetically homogeneous.